2020
DOI: 10.3855/jidc.10862
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Middle East Respiratory Syndrome Corona Virus in dromedaries and their traders in upper Egypt

Abstract: Introduction: Camel trade in Egypt depends mainly on importation. Seemingly healthy imported camels are responsible for the ingress of serious diseases into Egypt. A striking example of this concerning public health globally is the Middle East respiratory coronavirus (MERS-CoV) which causes case fatalities of over 34%. Here, we determined the seroepidemiological situation of the MERS-CoV in imported camels and their traders in Upper Egypt. Methodology: Sera of sixty-three dromedaries and twenty-eight camel tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(81 reference statements)
3
4
0
Order By: Relevance
“…Studies in wild bats, known reservoirs for pathogenic coronaviruses, have shown either similar seropositivity in males and females 44 , or higher seropositivity in female animals 45 . Similar studies in dromedary camels, the main reservoir host for MERS-CoV, showed higher seropositivity in females 46,47 . A possible explanation for the higher rate of seropositivity in females is the higher risk of exposure: the close proximity of female dromedaries to their highly susceptible calves puts them at repeated risk of infection 47 , while pregnant bats collect to stay warm during roosting season 45 .…”
Section: Review Of Sex Bias In Infection and Immunity 1 Sex Differensupporting
confidence: 73%
“…Studies in wild bats, known reservoirs for pathogenic coronaviruses, have shown either similar seropositivity in males and females 44 , or higher seropositivity in female animals 45 . Similar studies in dromedary camels, the main reservoir host for MERS-CoV, showed higher seropositivity in females 46,47 . A possible explanation for the higher rate of seropositivity in females is the higher risk of exposure: the close proximity of female dromedaries to their highly susceptible calves puts them at repeated risk of infection 47 , while pregnant bats collect to stay warm during roosting season 45 .…”
Section: Review Of Sex Bias In Infection and Immunity 1 Sex Differensupporting
confidence: 73%
“…Seropositivity in these reservoir animals, which act as hosts for viral pathogens but generally do not display symptoms, has been investigated with sampling studies.Studies in wild bats, known reservoirs for pathogenic coronaviruses, have shown either similar seropositivity in males and females45 , or higher seropositivity in female animals46 . Similar studies in dromedary camels, the main reservoir host for MERS-CoV, showed higher seropositivity in females47,48 . A possible explanation for the higher rate of seropositivity in females is the higher risk of exposure: the close proximity of female dromedaries to their highly susceptible calves puts them at repeated risk of infection48 , while pregnant bats collect to stay warm during roosting season 46 .2.…”
supporting
confidence: 74%
“…Similar studies in dromedary camels, the main reservoir host for MERS-CoV, showed higher seropositivity in females47,48 . A possible explanation for the higher rate of seropositivity in females is the higher risk of exposure: the close proximity of female dromedaries to their highly susceptible calves puts them at repeated risk of infection48 , while pregnant bats collect to stay warm during roosting season 46 .2. SEX DIFFERENCES IN OTHER INFECTIONSSex differences in response to infection occur at all ages with a generally higher burden of bacterial, viral, fungal and parasitic infections in human males.…”
supporting
confidence: 74%
“…6 MERS-CoV probably also originated from bats, 17 but the intermediate hosts are dromedary camels. Camel to human transmission of MERS-CoV may occur through contact with camels, unpasteurized camel milk, and medicinal use of camel urine, 19 but human to human transmission of the virus also occurs and has been documented in health care workers. 20 MERS has a much higher case fatality rate (about 35% for the 2500 patients with clinical infections 21,22 ).…”
Section: Comparison Of Covid With Other Coronavirus Outbreaksmentioning
confidence: 99%
“…42 Because bronchoalveolar lavage (BAL) fluid is sometimes obtained for viral identification [43][44][45] and is occasionally positive when nasopharyngeal and oropharyngeal swab samples are negative, 46 an aliquot may also be sent to the cytology laboratory. However, the cytologic findings of BAL samples of patients with COVID- 19 are not yet reported. In patients with MERS, cytological examination of BAL fluid reportedly showed high numbers of neutrophils and macrophages.…”
Section: Sars-cov-2 and The Cytology Laboratorymentioning
confidence: 99%